The Impact of Minimarket Existence on Grocery Store Revenue - Wati, Besse Mirna; Abidin, Zaenal; Yatima, Khusnul; Musthofa, M. Arif; Dewi, Hasna; Munip, Al; Mun'amah, Anatun Nisa (Zabags International Journal of Economy, 2025)
The existence of minimarkets spread across various areas, both urban and rural, has an impact on nearby grocery store traders, causing grocery store traders to experience a decline in income. Because the Indomaret minimarket is a small shop or supermarket that sells most of the daily necessities needed by consumers. Minimarkets are a favorite shopping place for people today who want light shopping but don't need to go far like to the supermarket. This research aims to find out whether there is a significant impact of the existence of minimarkets on grocery store income in Rantau Rasau sub-district. This research method uses a descriptive quantitative type, namely research that emphasizes analysis on numerical data (numbers) which are processed with a statistical model using a simple linear regression equation Y=a+bX. The sample size in this study was 60 respondents, namely grocery store traders around the Rantau Rasau sub-district. The results of this research state that the existence of minimarkets has a significant effect on grocery store income. We can see this: Tcount = 4.198 and Ttable = 1.980 with a significant value of 0.00003 < 0.05, which means it proves that Ho is rejected and Ha is accepted, which means that the existence of minimarkets in Rantau Rasau sub-district has a positive and significant effect on grocery store income.